Isolation and characterization of plant growth promoting bacteria isolated from andean soil as potential inoculants of soybean seeds - Belfiore, Carolina (2018)
Argentina is the leading exporter of soybean oil and flour, and the third largest producer of grain. Since, the crop isa matter of great importance to the national economy. Their production depends on the soil as their main resourceto ensure a good productive capacity, so it is necessary to preserve the physical, chemical and biological propertiesof the soil. Although, the indiscriminate use of chemical fertilizers, disturb them. In recent years, there has been atrend towards cleaner production to reduce the use of chemical. One of the alternatives involves biological meansthrough the use of plant growth promoting bacteria. These group of bacteria colonize the rhizosphere of plants andstimulate the plant growth by several mechanisms.The objective of this work was to characterize, identify and evaluate the growth promoting effect of 13 strainsisolated from the Andean vegetation rhizosphere. The bacterial isolates were Enterobacteria, Stenotrophomonas,Pseudomonas, Nocardiodes, Bacillus, Exiguobacterium, Acinetobacter and Lactococcus genera. The results of thebiochemical characterization determined that from the 13 bacterial strains, which produce siderophores, 11possess the catalase enzyme, 10 fixate nitrogen, 12 produce the protease enzyme, 12 solubilize phosphorus, and 11produce indoleacetic acid.The application of different inoculums to the seeds, allowed to obtain plants with longer stem length, moredeveloped roots, larger and more intense coloration leaves than the control plants. The results encourage deeperstudies to achieve the formulation of inoculums to use as a biofertilizer, which would replace chemical fertilizersor reduce their doses.